PENERAPAN MODEL PEMBELAJARAN KOOPERATIF TIPE COURSE REVIEW HORAY (CRH) UNTUK MENINGKATKAN HASIL BELAJAR MATEMATIKA SISWA KELAS VIII3 SMP NEGERI 4 TAPUNG - Fatma Kumala; Sehatta Saragih; Nahor Murani Hutapea (Jurnal Online Mahasiswa (JOM) Bidang Keguruan dan Ilmu Pendidikan, 2016)
Abstract: This research was classroom action research that aims to improve learning process and mathematics learning outcomes with applied the cooperative learning type of Course Review Horay (CRH). The subject of the research were students of class VIII3 SMP Negeri 4 Tapung in the second semester academic years 2014/2015. There are 24 students in the class, with the heterogenous level. The research are two cycles, each a cycle has four stages, that are planning, implementation, observation, and reflection. Instrument to collect the data are observation and mathematics achivement test. The observation data analyzed by using descriptive and qualitative, and for students’ test by using descriptive and quantitative. The qualitative analysis showed an improvement of learning process prior to action to the first cycle and second cycle. The results of this research showed an increase in students achievement from the based-score with the percentage 29,16% to 45,83% on the first test and 70,83% on the second test. Based on the finding can be concluded the implentation of applied the cooperative learning type of Course Review Horay (CRH) to improve students’ mathematics achievement at class VIII3 SMP Negeri 4 Tapung in the second semester academic years 2014/2015.Key words: Mathematics learning outcome, Cooperative learning, Course Review Horay, Class action research